Implementation of Discovery Learning Strategies in Learning Student’s Reading Skills at Islamic Senior High School 1 Kediri - Umi Zahroh Malichayati, Zahroh; Idham Romi, Ahmad (Naatiq: Journal of Arabic Education, 2024)
This research is motivated by the success of public junior high schools in Kediri city in bringing their students to achieve different achievements in Arabic for academic and non-academic domains, especially in reading skills. This study aims to identify the planning of learning reading skills based on discovery learning strategies, describe the implementation of learning reading skills based on discovery learning strategies, determine the impact of learning reading skills based on discovery learning strategies, and determine the effect of learning reading skills based on discovery learning strategies. This research is a qualitative field research. Data were collected through observation, interview, and documentation. The data were analyzed by data reduction, data presentation, and conclusion/verification. The findings of this research are as follows: Learning planning for reading skills based on discovery learning is in the form of developing lesson plans that are adjusted to the student's circumstances. The learning of reading skills is carried out through the stages of applying the discovery learning model and additional collaboration by the teacher, and the impact of discovery learning on learning reading skills in public junior high schools in Kediri city is an increase in students' active behavior in self actualization in reading comprehension Discovery Learning; Reading Skills; Arabic